Aplikasi Pemandu Wisata Kebun Binatang Surabaya Berbasis Android - Andreanto, Reo; Sutanto, Teguh; Taufik, Vicky M. (Jurnal JSIKA, 2012)
Surabaya Zoo is one of the garden cultivation and propagation of flora and fauna which is located in the center of Surabaya. Surabaya Zoo commonly abbreviated KBS has many types of flora and fauna in it, so the KBS to be one of Surabaya citizens in tourist visits during the holiday weekend. The zoo is located at No. Setail road. 1 Surabaya is one of the famous zoos in Indonesia. Different types of animals and plants bred and cultivated in the zoo, so that people can watch with a very complete collection of wildlife and plants that exist. Many also a collection of rare animals are also available on Surabaya zoo´s beloved residents, Given the extent and the large number of collections of animals at Surabaya Zoo needed a tour guide based android application to become a personal tour guide for visitors to these attractions. Application Tour Guide Surabaya Zoo has several facilities including digital maps and routes to help visitors to enjoy the visit and also contains information about the animal and public facilities are available in the area of ​​Surabaya Zoo. Making it easier for visitors to visit sights in Surabaya Star Gardens. Keywords: android, digital map ,digital route, tour guide.